Continuous Compliance, Encryption, and Security on AWS (The DevSecOps Series on AWS) - Duvall, Paul (Addison-Wesley Professional, 2021)
Overview Continuous Compliance, Encryption, and Security on AWS is a series of video courses that will help you use AWS services to define compliance and encryption as code, and to create an end-to-end continuous security solution. These services include AWS Config Rules, Amazon EventBridge Rules, AWS CloudFormation, AWS CodePipeline, AWS Lambda, AWS Key Management Service, AWS CodeCommit, AWS CodeBuild, AWS Step Functions, AWS Organizations, AWS Security Hub, Amazon GuardDuty, Amazon Inspector, AWS Secrets Manager, Amazon VPC, Amazon Macie, AWS Audit Manager, and many others. You will learn how to use a combination of these tools to prevent, detect, encrypt, and remediate noncompliant resources in your software systems. The videos in this series will also help you apply design principles for security and build continuous security solutions. Paul Duvall has multiple AWS certifications including AWS Certified Security - Specialty. He has architected, implemented, and managed software and systems solutions for more than 20 years. Throughout the series, you will have the opportunity to work along with Paul as he demonstrates how to automate the provisioning, encryption and security of these services, and how to include them as part of a deployment pipeline using AWS CloudFormation and AWS CodePipeline. Courses include Continuous Compliance on AWS (The DevSecOps on AWS Series) LiveLessons (Video Training) Continuous Encryption on AWS (The DevSecOps on AWS Series) LiveLessons (Video Training) Continuous Security on AWS (The DevSecOps on AWS Series) LiveLessons (Video Training) Skill Level Intermediate to Advanced Learn How To Apply key compliance, encryption, and security concepts on AWS. Use AWS services and tools to automate compliance, encryption, and security into your software delivery process. Who Should Take This Course Software developers and security and compliance professionals who want to integrate compliance, encryption, and security into every facet of the software development and delivery process. Professionals with a working knowledge of AWS and programming experience who want to make compliance, encryption, and security ubiquitous across their systems. Course Requirements Working knowledge of AWS (for example, 1-2+ years working with AWS). Knowledge of AWS CloudFormation. Practical experience with high-level programming experience, such as Python, Java, Node.js, etc. is helpful. About the Author Paul Duvall was a founder and CTO of ...